Konstruksi Jurnalis Profesional Dalam Drama Korea Hush - Siregar, Indah Sonia; Rasyid, Abdul; Zuhriah (Prisani Cendekia Institute, 2023)
The purpose of this study is to find out how the construction of professional journalists applies the nine elements of journalism in the Korean drama Hush. The theory used to explore this research is the theory of media construction and the nine elements of journalism, and content analysis. The object of this research is the 16 episodes of the Korean drama Hush. The method used in this research is a qualitative method with a descriptive paradigm. The analysis technique used is content analysis technique. The results of the study show that there is a construction of a professional journalist in the Korean drama Hush. The journalists constructed in the play correspond to the nine elements of journalists Bill Kovach and Tom Rosenstiel, namely; seeking the truth (6 scenes), placing loyalty to citizens (6 scenes), Discipline in verifying (3 scenes), Independent from sources of coverage (5 scenes), Journalists carry out the task of monitoring power (1 scene), Journalism as a public forum (1 scene), Journalism must be attractive and relevant (2 scenes), proportional and comprehensive news (3 scenes), and listen to one's conscience (8 scenes).